Perancangan Enterprise Architecture Pada Bidang Distribusi Di Pt. Pln Distribusi Jawa Barat Menggunakan Framework Togaf Adm - Recsa Andriyani Putri; Yuli Adam Prasetyo; Faishal Mufied Al Anshary (eProceedings of Engineering, 2016)
PT. PLN Distribusi Jawa Barat company supplying electricity to reach over 42,196 km which includes the province of West Java. Number of consumers which reaches more than 9 million costumers, or 22% of the costumers number PLN nationally, make PLN DJB is a largest unit electricity company PLN was in Indonesia. The distribution of electrical energy transmission up to subscribers was the principal activity conducted by PLN DJB. The distribution of electricity to produce value for customers PLN DJB company. Enterprise architecture is one of the methods that can be used to harmonize business strategy and strategies ti designed as required by business. TOGAF ADM is one of a framework that can be used as reference in establishing the enterprise architecture. Output of research is blueprint architecture business, data, application of technology and roadmap development TI in PLN DJB. Expected , with the design enterprise architecture on the distribution in PLN DJB can be reference develop the distribution of both in terms of business and information technology. Keywords: Enterprise Architecture, TOGAF ADM, Energy Company